Caracterização de queijos coloniais de propriedades rurais do Vale do Taquari/RS - Erhardt, Magnólia Martins (2023)
The production of artisanal cheese has been valued by consumers, especially when these products rescue traditional and culturally established production processes from generation to generation, which increases demand, although they still lack standardization, exposing the consumer population to important microbiological issues. This study analyzed artisan cheeses produced from raw milk in the first stage, following 5 properties in a city in the Taquari Valley region, regarding the good manufacturing practices (GMP) adopted, the various maturation periods, and the physicochemical and microbiological characteristics. The physical-chemical analyses identified that most of the products had high humidity (46 to 54.9%) and presented nonconformities for some indicators; in the microbiological aspect, through the Petrifilm methods (3M Brazil), 100% of the samples were unfit for consumption due to contamination by Staphylococcus aureus and/or Total coliforms and/or Escherichia coli. In a second step, artisanal products were purchased in local markets, which were submitted to analysis by time domain mass spectrometry (MALDI-TOF MS) techniques, to identify bacteria and fungi directly from isolates obtained from the culture plates, and by the next-generation sequencing (NGS) method, amplifying the V3/V4 region of the 16S rRNA gene. In the proteomic analysis, the species identified were Staphylococcus aureus and Lactococcus lactis, and the majority (68.18%) of the strains were species of the Enterobacteriaceae family, with a predominance of the genera Escherichia, Enterobacter, Klebsiella, and Escherichia coli. In the metagenomic analyses, the diversity of 18 lactic acid bacteria (LAB) was characterized. The BAL genera identified in the cheese samples were Bavariicococcus, Enterococcus, Lactobacillus, Lactococcus, Leuconostoc, Marinillactibacillus and Pediococcus. Lactococcus lactis was the predominant species, present in all samples. The abundance varied according to geographical environments, with the highest observed at high altitudes. The results showed that while this specific microbiota contributes to the unique flavor and characteristics of regional dairy products, it can also be a source of specific starter cultures that ensure product identity. All isolates identified by MALDI-TOF MS were at the species level, revealing that the method is quite discriminatory at this level of classification. The metagenomic analyses showed that the diversity of BALs was not so wide, with 35 species distributed in seven genera; however, they represented 60% of the total bacterial composition of the samples. The most abundant genera were Lactococcus, which deserves to be highlighted for having the highest diversity of species (total of 14) and presenting a statistical correlation with the abundance of BALs, and Enterococcus, which were present in all samples. At the species level, Lactococcus lactis was the most representative. The identification of bacterial species in fermented cheeses is important, as it contributes significantly to organoleptic quality in the ripening process, establishing shelf life and including the safety and overall quality of the cheese. Knowledge of the specific bacterial microbiota of this type of cheese allows the flavor and unique characteristics of the regional dairy product to be preserved and can produce specific lactic ferments that guarantee the identity of the product. However, the importance of the results is reinforced for the need to intensify issues related to GMP, sanitary standards with greater control in the production stages of artisanal cheese, and the evaluation of the raw material, so that the product meets the identity and quality parameters suitable for human consumption.